2016
DOI: 10.1093/cercor/bhw228
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic Bias Modulates Interpretation of Speech via Neural Delta-Band Oscillations

Abstract: Language comprehension requires that single words be grouped into syntactic phrases, as words in sentences are too many to memorize individually. In speech, acoustic and syntactic grouping patterns mostly align. However, when ambiguous sentences allow for alternative grouping patterns, comprehenders may form phrases that contradict speech prosody. While delta-band oscillations are known to track prosody, we hypothesized that linguistic grouping bias can modulate the interpretational impact of speech prosody in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
188
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(210 citation statements)
references
References 79 publications
18
188
3
1
Order By: Relevance
“…After the chunk structure is parsed, the listener could synchronize their attention and predictions to the sequence. Previous studies have suggested that entrained neural oscillations may reflect both sequence parsing (Ding et al, 2016;Kösem et al, 2016;Meyer et al, 2016;Wang et al, 2017;Meyer and Gumbert, 2018) and temporal attention/prediction (Morillon and Baillet, 2017;Jin et al, 2018;Rimmele et al, 2018), and could causally modulate speech perception (Kösem et al, 2018;Riecke et al, 2018;Zoefel et al, 2018). The current results cannot distinguish which chunk-related process drives the chunk-rate response.…”
Section: Rule-based Chunking Hypothesiscontrasting
confidence: 85%
See 1 more Smart Citation
“…After the chunk structure is parsed, the listener could synchronize their attention and predictions to the sequence. Previous studies have suggested that entrained neural oscillations may reflect both sequence parsing (Ding et al, 2016;Kösem et al, 2016;Meyer et al, 2016;Wang et al, 2017;Meyer and Gumbert, 2018) and temporal attention/prediction (Morillon and Baillet, 2017;Jin et al, 2018;Rimmele et al, 2018), and could causally modulate speech perception (Kösem et al, 2018;Riecke et al, 2018;Zoefel et al, 2018). The current results cannot distinguish which chunk-related process drives the chunk-rate response.…”
Section: Rule-based Chunking Hypothesiscontrasting
confidence: 85%
“…In terms of the neural basis, fMRI studies have demonstrated that distributed brain areas are involved in grouping words into chunks (Friederici et al, 2000;Lerner et al, 2011;Pallier et al, 2011;Bulut et al, 2017). MEG and EEG studies have suggested that low-frequency neural activity tracks linguistic structures (Ding et al, 2016;Meyer et al, 2016;Martin and Doumas, 2017;Meyer and Gumbert, 2018). Recent work suggests that animals can also parse motor sequences into hierarchically organized chunks (Geddes et al, 2018;Jiang et al, 2018).…”
Section: Rule-based Chunking Hypothesismentioning
confidence: 99%
“…65 Indeed, the brain 412 tracks phrase and sentence boundaries even when speech is devoid of prosody but only if it is 413 comprehensible; 39 and the phase of below-4-Hz brain oscillations modulates perception of 414 ambiguous sentences. 37 CTS at phrasal/sentential rate would help align neural excitability with 415 syntactic information to optimize language comprehension. 36 In contrast, CTS at syllable rate 416 (here taken as 2-8 Hz) would reflect low level auditory processing.…”
Section: Does Phonological Awareness Mediate Sin Perception Capacitiementioning
confidence: 99%
“…It resulted in an empirical definition of delta (2-3.5 Hz), theta (4-7 Hz), alpha (8)(9)(10)(11), and gamma bands (50-110 Hz). Although not prominent neither in the sEEG dataset nor in the MEG dataset, we added a beta band (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) Hz) based on existing literature. Indeed, previous works have shown coupling of the beta band power with the phase of the stimulus envelope at similar paces 31,92 .…”
Section: Definition Of Canonical Frequency Bands Based On Auditory Comentioning
confidence: 99%